2014
DOI: 10.1039/c3ob41992d
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, structural characterization and reactivity of heteroazuliporphyrins

Abstract: A series of hetero-azuliporphyrins have been prepared by the "3 + 1" variant on the MacDonald condensation. Azulitripyrranes with tert-butyl and phenyl substituents reacted with thiophene or selenophene dialdehydes in the presence of TFA to give, following an oxidation step, thia- and selena-azuliporphyrins in 45-55% yield. Two of these compounds gave crystals suitable for X-ray crystallographic analysis and the data were consistent with the presence of a 17-atom delocalization pathway. The hetero-azuliporphyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(32 citation statements)
references
References 29 publications
1
31
0
Order By: Relevance
“…Thus, 5,20-diphenyl-10,15-ditolyl-23-thiaazuliporphyrin maintains borderline aromaticity, comparable to βand 10,15-diaryl-substituted analogues. 10,11 This difference significantly grows upon mono- , respectively (600 MHz, CD 2 Cl 2 , 190 K)]. Two canonical structures of 1 describe the π-electron macrocyclic delocalization (Scheme 4).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, 5,20-diphenyl-10,15-ditolyl-23-thiaazuliporphyrin maintains borderline aromaticity, comparable to βand 10,15-diaryl-substituted analogues. 10,11 This difference significantly grows upon mono- , respectively (600 MHz, CD 2 Cl 2 , 190 K)]. Two canonical structures of 1 describe the π-electron macrocyclic delocalization (Scheme 4).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Carbaporphyrinoids provide an intriguing environment for advanced investigations of organometallic reactivity confined to a unique macrocyclic environment . Azuliporphyrinoids (Scheme ), in which one or more porphyrinic pyrrole rings are replaced by the azulene fragment (β-substituted azuliporphyrins, β-substituted 23-heteroazuliporphyrins (O, S, Se), , 10,15-diaryl-23-heteroporphyrins (S, Se), 5,10,15,20-tetraarylazuliporphyrin, 5,10,15,20-tetraaryl-22,24-diheterodiazuliporphyrin (O, S), , and 5,10,15,20-tetraaryltetraazuliporphyrin tetracation), can be considered as the stimulating class of synthetically readily accessible porphyrinoids designed to explore different facets of organometallic azulene coordination triggered by specific macrocyclic support.…”
Section: Introductionmentioning
confidence: 99%
“…Lash et al reported the syntheses of thia/selena azuliporphyrins and oxacarbaporphyrins (Scheme 20). 55 These macrocycles 90 / 91 revealed several moderate bands in the Soret band region at 372, 384, 448, and 477 nm, together with broad absorption bands between 500 and 800 nm (Fig. 20).…”
Section: Azulene Amended Aromatic Carbaporphyrinoids and Expanded Carbaporphyrinoids With Nir Absorptionmentioning
confidence: 94%
“…[30] Modified tripyrrane-like intermediates have also been utilized in the synthesis of heterocarbaporphyrins and dicarbaporphyrinoid systems. For instance, azulitripyrranes 8 reacted with furan, thiophene, and selenophene dialdehydes to give oxa-, thia-, and selena-azuliporphyrins 9, [27,[31][32][33] while the reaction of 8 with indene dialdehyde 10 afforded the dicarbaporphyrinoid 11 (Scheme 3). [27] In addition, "2 + 2" MacDonald-type condensations have been used to prepare mono-and dicarbaporphyrinoids.…”
Section: Synthesis Of Carbaporphyrinoid Systemsmentioning
confidence: 99%